1993
DOI: 10.1200/jco.1993.11.4.690
|View full text |Cite
|
Sign up to set email alerts
|

Granulocytic sarcoma is associated with the 8;21 translocation in acute myeloid leukemia.

Abstract: Our data suggest that this association is more common than generally recognized and may be specific. Patients with t(8;21) should be observed closely for signs and symptoms of granulocytic sarcoma. These patients may have a less favorable prognosis than other patients with t(8;21). Cooperative oncology groups should retrospectively identify patients with AML and t(8;21) who had a poor outcome to determine if they had a disproportionate incidence of granulocytic sarcoma. If so, aggressive therapy such as bone m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
134
3
3

Year Published

1996
1996
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(150 citation statements)
references
References 47 publications
8
134
3
3
Order By: Relevance
“…Tallman et al 4 suggested that these patients might have a less favorable prognosis than AML patients with this translocation but no GS. The prognosis for untreated GS is poor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tallman et al 4 suggested that these patients might have a less favorable prognosis than AML patients with this translocation but no GS. The prognosis for untreated GS is poor.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Nonmyeloablative allogeneic stem cell transplantation has been reported by Slavin et al 5 to eradicate malignant host hematopoietic cells successfully. The aim of nonmyeloablative conditioning is to engraft donor immunohematopoietic cells to establish host-versus-graft tolerance for induction of graft-versus-malignant (GVM) effects to displace residual malignant host cells.…”
mentioning
confidence: 99%
“…The incidence of granulocytic sarcoma is similar in acute and chronic granulocytic leukemia [17]; and fourfold higher in myelogenous leukemia FAB M2, characterized by typical chromosomic translocation T 8;21, than in the general leukemic population [34,35]. The development of granulocytic sarcoma in patients with leukemia implies a poor prognosis, often heralding a blastic crisis [23].…”
Section: Discussionmentioning
confidence: 99%
“…We have reported in recent past few rare sites of MS like mediastinum, pleura, spinal cord and orbit [8][9][10][11]. Much rarer is [7,8,[10][11][12]. Female genital tract is also one of the rare site of involvement in acute leukaemia.…”
mentioning
confidence: 99%
“…Myeloid sarcoma can (1) be isolated (2) precede AML (3) coincide with AML (4) represent blast transformation of MPN's or (5) represent a relapse in a previously treated AML. Studies have shown that t (8; 21) and inversion (16) are the two most common cytogenetic abnormalities detected in cases of AML with granulocytic sarcomas [12]. Commonly, FAB subtype M4 and M5 are mostly associated with extra medullary tissue involvement.…”
mentioning
confidence: 99%